Sodium Butyrate: A Multifaceted Modulator in Colorectal Cancer Therapy - Alexandra Laura Mederle; Alexandra Semenescu; George Andrei Drăghici; Cristina Adriana Dehelean; Nicolae-Valentin Vlăduț; Dragoş Vasile Nica (Medicina)
Background and Objectives: Sodium butyrate (NaB) is a potent modulator of cancer-related gene networks. However, its precise mechanisms of action and effects at elevated doses remain insufficiently explored. This study investigated the impact of NaB at physiologically relevant doses on key cellular metrics (viability, confluence, cell number, morphology, nuclear integrity) and a comprehensive set of apoptosis and proliferation regulators (including underexplored genes) in colorectal cancer (CRC) cells. Materials and Methods: Human HCT-116 cells were treated with increasing NaB concentrations (0–20 mM). Cell viability, confluence, number, morphology, and nuclear integrity were assessed using MTT and imaging assays. RT-PCR was used to determine changes in the expression of critical pro-apoptotic players (BAX, CASP3, PUMA, TP53), anti-apoptotic facilitators (BCL-2, MCL-1), cell division regulators (PCNA, Ki-67, CDKN1), and inflammation genes (NF-κB). Results: This study provides the first exploration of MCL-1 and PCNA modulation by NaB in the context of CRC and HCT-116 cells, offering significant translational insights. All treatments reduced cell viability, confluence, and number in a dose-dependent manner (p < 0.0001). Gene expression revealed dose-related increases in most pro-apoptotic markers (BAX, CASP3, PUMA; p < 0.001), and decreases for the other genes (p < 0.001). BAX emerged as the most responsive gene to NaB, while TP53 showed minimal sensitivity, supporting NaB’s effectiveness in p53-compromised phenotypes. Nuclear condensation and fragmentation at higher NaB doses confirmed apoptotic induction. Conclusions: NaB can modulate critical apoptotic and cell cycle genes, disrupt tumor cell proliferation, and overcome resistance mechanisms associated with anti-apoptotic regulators such as MCL-1. By targeting both short-term and long-term anti-apoptotic defenses, NaB shows promise as a preventive and therapeutic agent in CRC, particularly in high-risk phenotypes with compromised p53 functionality. These findings support its potential for integration into combination therapies or dietary interventions aimed at enhancing colonic butyrate levels.